STUDENTS MISCONCEPTION: THE DEVELOPING OF SOCRATIC DIALOGUE MEDIA ON TEMPERATURE AND HEAT - Sujito Sujito; Irvany Nurita Pebriana; Hestiningtyas Yuli Pratiwi; Abdul Hayyi; Kadim Masjkur; Asim Asim; Sutopo Sutopo (Program Studi Pendidikan IPA, Fakultas Ilmu Pendidikan, Universitas Trunojoyo Madura, 2018)
This purpose of this study is to improve media of Socratic dialogue that has been developed by the previous researcher and to determine the effect of the Socratic dialogue in enhance understanding of heat concept. As a result of prior research, showed students still have a misconception. Data collected from one institution of high school in Malang City using pre and posttest. Student’s conceptual changes that occur previous, during, after will be analyzed based on pretest and posttest scores and rethinking sequence of used record Socratic dialogue media. To explore more in-depth, the researcher conducted interviews with students on this concept. This result showed Socratic dialogue media could help students be aware mistakes or students become convinced if their opinion is correct. This study is important because it uses to improve student’s comprehension to move from the false toward the right concept. In some cases, the result of this study used for recovery and prevent to misconception. It can solve with appear cognitive conflict in the minds of students through Socratic dialogue.